Harnessing the health systems strengthening potential of quality improvement using realist evaluation: an example from southern Tanzania. (6th November 2020) - Manzi, Fatuma; Marchant, Tanya; Hanson, Claudia; Schellenberg, Joanna; Mkumbo, Elibariki; Mlaguzi, Mwanaidi; Tancred, Tara
Abstract: Quality improvement (QI) is a problem-solving approach in which stakeholders identify context-specific problems and create and implement strategies to address these. It is an approach that is increasingly used to support health system strengthening, which is widely promoted in Sub-Saharan Africa. However, few QI initiatives are sustained and implementation is poorly understood. Here, we propose realist evaluation to fill this gap, sharing an example from southern Tanzania. We use realist evaluation to generate insights around the mechanisms driving QI implementation. These insights can be harnessed to maximize capacity strengthening in QI and to support its operationalization, thus contributing to health systems strengthening. Realist evaluation begins by establishing an initial programme theory, which is presented here. We generated this through an elicitation approach, in which multiple sources (theoretical literature, a document review and previous project reports) were collated and analysed retroductively to generate hypotheses about how the QI intervention is expected to produce specific outcomes linked to implementation. These were organized by health systems building blocks to show how each block may be strengthened through QI processes. Our initial programme theory draws from empowerment theory and emphasizes the self-reinforcing nature of QI: the more it is implemented, the more improvements result, further empowering people to use it. We identified that opportunities that support skill- and confidence-strengthening are essential to optimizing QI, and thus, to maximizing health systems strengthening through QI. Realist evaluation can be used to generate rich implementation data for QI, showcasing how it can be supported in 'real-world' conditions for health systems strengthening.